2019
DOI: 10.1002/cam4.2670
|View full text |Cite
|
Sign up to set email alerts
|

A community‐based lung cancer rapid tissue donation protocol provides high‐quality drug‐resistant specimens for proteogenomic analyses

Abstract: BackgroundFor the advancement of cancer research, the collection of tissue specimens from drug‐resistant tumors after targeted therapy is crucial. Although patients with lung cancer are often provided targeted therapy, post‐therapy specimens are not routinely collected due to the risks of collection, limiting the study of targeted therapy resistance mechanisms. Posthumous rapid tissue donation (RTD) is an expedient collection process that provides an opportunity to understand treatment‐resistant lung cancers.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This allows for the detection of rare and novel fusions. For example, an expected EML4-ALK fusion and an unexpected AGK-BRAF fusion was detected in a lung cancer sample harboring a known EML4-ALK fusion at Laboratory A during the TST170 validation and was confirmed by orthogonal testing with a different NGS assay ( Boyle et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…This allows for the detection of rare and novel fusions. For example, an expected EML4-ALK fusion and an unexpected AGK-BRAF fusion was detected in a lung cancer sample harboring a known EML4-ALK fusion at Laboratory A during the TST170 validation and was confirmed by orthogonal testing with a different NGS assay ( Boyle et al, 2020 ).…”
Section: Resultsmentioning
confidence: 97%
“…However, there is significant debate in the field whether a tumor biopsy represents the phenotype of all metastatic sites, and CTCs may provide the opportunity to evaluate cancer cells shed from all sites of disease. Heterogeneity in PD-L1 expression between metastatic sites has been observed with rapid autopsy studies of patients with metastatic prostate cancer [ 38 ] and in rapid post-mortem tissue donated from patients with NSCLC [ 39 ]. While some studies have shown correlation in the expression of PD-L1 on solid tissue biopsy compared to liquid biopsy [ 40 ], several publications have demonstrated discordance [ 41 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutant non-small cell lung cancers are resistant to EGFR tyrosine kinase inhibitor (EGFR-TKI) (Westover et al, 2018), and BRAF fusion is one of the reasons for their resistance (Yu et al, 2013). Lung cancer patients show secondary resistance to EGFR TKIs due to acquired AGK/BRAF fusion (Vojnic et al, 2019;Boyle et al, 2020), which suggests that AGK is involved in some acquired tumor resistance, but the specific AGK mechanism in this context needs to be clarified.…”
Section: Drug Resistancementioning
confidence: 99%